2022
DOI: 10.32526/ennrj/20/202100200
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in the Inlet and Outlet Networks of Rawa Jombor Reservoir: Accumulation in Aquatic Fauna, Interactions with Heavy Metals, and Health Risk Assessment

Abstract: Streams are regarded as a pathway for spreading microplastics from land to various aquatic systems. The contamination of streams connected to the Rawa Jombor Reservoir may increase microplastic concentrations in the reservoir. The water coming out of the reservoir carries microplastics that spread out into the stream networks around the reservoir. Heavy metals have a high affinity for microplastics, increasing metal burdens on the surface of microplastics. The transfer of microplastics along the food chain lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Increased human population and anthropogenic activities inevitably cause MP pollutants in the environment [3]. MP accumulation in aquatic fauna is generally internal as a result of oral ingestion, filter feeding, respiration, and dermal contact with water and sediment [4]. Many studies have revealed that benthic invertebrates, fishes, and aquatic mammals are at risks for MP accumulation, which can cause a blockage of the digestive tract and inflammatory responses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Increased human population and anthropogenic activities inevitably cause MP pollutants in the environment [3]. MP accumulation in aquatic fauna is generally internal as a result of oral ingestion, filter feeding, respiration, and dermal contact with water and sediment [4]. Many studies have revealed that benthic invertebrates, fishes, and aquatic mammals are at risks for MP accumulation, which can cause a blockage of the digestive tract and inflammatory responses [5].…”
Section: Introductionmentioning
confidence: 99%
“…Intensive use of plastic films can induce contamination of microplastics and phthalate esters (PAEs) (Li et al, 2021). Reduction of microplastics contamination is related to the management and mitigation of microplastics pollution (Rahmayanti et al, 2022). However, Phthalic acid esters (PAEs) are extensively used in plastic materials (Zhu et al, 2022), such as, polyvinyl chloride, medical product, cosmetics, clothing, building materials, paints, pesticides, fertilizers, food packaging (Staples et al, 1997;Xu et al, 2008;Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%